Development of a Prognostic Alternative Splicing Signature Associated With Tumor Microenvironment Immune Profiles in Lung Adenocarcinoma - Bao, Guangyao; Li, Tian; Guan, Xiaojiao; Yao, Yao; Liang, Jie; Xiang, Yifan; Zhong, Xinwen (Frontiers in Oncology, 2022)
Background: Alternative splicing (AS), a pivotal post-transcriptional process across over 95% human transcripts, involved in transcript structural variations and protein complexity. Clinical implication of AS events and their interaction with tumor immunity were systematically analyzed in lung adenocarcinoma (LUAD). Methods: Transcriptome profiling as well as AS data of LUAD were retrospectively curated. Then, the network of the overall survival (OS)-relevant AS events with splicing factors was established. After screening OS-relevant AS events, a LASSO prognostic model was conducted and evaluated with ROC curves. A nomogram that integrated independent prognostic indicators was created. Immune response and immune cell infiltration were estimated with ESTIMATE, CIBERSORT and ssGSEA algorithms. Drug sensitivity was inferred with pRRophetic package. Results: In total, 2415 OS-relevant AS events were identified across LUAD patients. The interaction network of splicing factors with OS-relevant AS events uncovered the underlying regulatory mechanisms of AS events in LUAD. Thereafter, a prognostic model containing 12 AS events was developed, which acted as a reliable and independent prognostic indicator following verification. A nomogram that constituted stage and risk score displayed the great effectiveness in evaluating the survival likelihood. Moreover, the AS-based prognostic model was in relation to immune response and immune cell infiltration. Patients with high risk score displayed therapeutic superiority to cisplatin, erlotinib, gefitinib, and gemcitabine. Finally, three AS-relevant genes (CDKN2A, TTC39C, and PKIB) were identified as prognostic markers. Conclusion: Collectively, our findings developed an AS event signature with powerful prognostic predictive efficacy in LUAD.